Are We Experienced? Reflections on the SUNY Experiential Learning Mandate. (March 2018) - Isaak, Jerry; Devine, Michael; Gervich, Curt; Gottschall, Richard
Background: The State University of New York (SUNY), the nation's largest comprehensive public university system, recently proposed making experiential learning activities available to all students enrolled in an academic program. Each campus was tasked with examining the feasibility of including experiential learning activities as a degree requirement. The Plattsburgh campus faculty senate voted to reject this requirement.Purpose: In light of the Plattsburgh rejection of the SUNY mandate, this study seeks to examine the practice and perspectives of four Plattsburgh faculty through the lens of a single experiential learning assignment.Methodology/Approach: A case study approach was used to illuminate common and/or distinctive pedagogies of instructors across four disciplines.Findings/Conclusions: Common themes include the elements of choice, embodiment, relationships, and risk. Critical to each case study was the willingness and ability of the instructor to engage in the educational process as a participant and expert learner.Implications: If the state, university system, or campus seeks to mandate experiential/applied learning, the mandate should be focused on the pedagogical components of experiential education not on the types of activities that count.